A novel approach with matrix based public key crypto systems. (17th February 2017) - Krishna, Addepalli V. N.; Narayana, Addepalli Hari; Madhura Vani, K.
Abstract: Here in this model, a new mechanism is used for Public Key Cryptography. A generator matrix is used to generate a field with a large prime number. The generator matrix, prime number and quaternary vector are used as global variables. The Generator Matrix is powered by a private key to generate Public Key. Since the model is based on Discrete Logarithm Problem, which is Hard problem, the proposed algorithm supports the features like Authenticity of users, Security & Confidentiality of data transmitted. Going by the construction of the algorithm, Encryption is being done on blocks of data for which it consumes less computing resources. Going by complexity of the algorithm, the key length needed is about 72 bit lengths to provide sufficient strengths against crypto analysis.